Identification of loss-of-function RyR2 mutations associated with idiopathic ventricular fibrillation and sudden death. Issue 4 (30th April 2021) - Zhong, Xiaowei; Guo, Wenting; Wei, Jinhong; Tang, Yijun; Liu, Yingjie; Zhang, Joe Z.; Tan, Vern Hsen; Zhang, Lin; Wang, Ruiwu; Jones, Peter P.; Napolitano, Carlo; Priori, Silvia G.; et al.
Abstract: Mutations in cardiac ryanodine receptor (RyR2) are linked to catecholaminergic polymorphic ventricular tachycardia (CPVT). Most CPVT RyR2 mutations characterized are gain-of-function (GOF), indicating enhanced RyR2 function as a major cause of CPVT. Loss-of-function (LOF) RyR2 mutations have also been identified and are linked to a distinct entity of cardiac arrhythmia termed RyR2 Ca 2+ release deficiency syndrome (CRDS). Exercise stress testing (EST) is routinely used to diagnose CPVT, but it is ineffective for CRDS. There is currently no effective diagnostic tool for CRDS in humans. An alternative strategy to assess the risk for CRDS is to directly determine the functional impact of the associated RyR2 mutations. To this end, we have functionally screened 18 RyR2 mutations that are associated with idiopathic ventricular fibrillation (IVF) or sudden death. We found two additional RyR2 LOF mutations E4146K and G4935R. The E4146K mutation markedly suppressed caffeine activation of RyR2 and abolished store overload induced Ca 2+ release (SOICR) in human embryonic kidney 293 (HEK293) cells. E4146K also severely reduced cytosolic Ca 2+ activation and abolished luminal Ca 2+ activation of single RyR2 channels. The G4935R mutation completely abolished caffeine activation of and [ 3 H]ryanodine binding to RyR2. Co-expression studies showed that the G4935R mutation exerted dominant negative impact on the RyR2 wildtype (WT) channel. Interestingly, the RyR2-G4935R mutant carrier had a negative EST, and the E4146K carrier had a family history of sudden death during sleep, which are different from phenotypes of typical CPVT. Thus, our data further support the link between RyR2 LOF and a new entity of cardiac arrhythmias distinct from CPVT.